Código de modernidade e sistemas antigos: a propósito do uso da informática pelos professores de matemática da rede pública estadual em Belém - PEREIRA, Franz Kreüther (2005)
The use of the technologies of Information and Communication TIC at the scholar environment, besides allow the access to one universe of informations so chaotic than unimaginable, promoted a deep transformation in the relation of your main actors teachers and students with knowledge. Since the end of 80s that, in Brazil, many programs appears with the objective of to provide to the public education equals conditions with the private education, searching through the insert at the schools from municipal and state; a technologic environment for learning. Based on the use of computers connecting to the Internet enabling a jump of quality of the public education. The purpose of this search is inspect if the teachers of Mathematic - acting at the public schools in Belém/PA that has Informatic Laboratory - create proceedings with that technologic to find better ways for your pedagogical praxis; favouring the transmission of informations to the build of knowledge and Math concepts.